Comparative analysis of resource utilization in integrative anthroposophic and all German pediatric inpatient departments - Katharina Fetz; Alfred Längler; Melanie Schwermer; Clara Carvalho-Hilje; Jan Vagedes; Tycho Jan Zuzak; Thomas Ostermann (BMC, 2020)
Abstract Background Integrative Medicine (IM) combines conventional and complementary therapies. It aims to address biological, psychological, social, spiritual and environmental aspects of patients' health. During the past 20 years, the use and request of IM in children and adults has grown. Anthroposophic Medicine (AM) is an IM approach frequently used in children in Germany. From both public health and health economic perspectives, it is relevant to investigate whether there are differences in the resource utilization between integrative pediatric departments (IPD) and the entirety of all pediatric departments. Methods Standard ward documentation data from all German integrative anthroposophic pediatric departments (2005-2016; N = 29,956) is investigated and systematically compared to data of the entirety of all pediatric departments in Germany derived from the Institute for the Hospital Reimbursement System (2005-2016, N = 8,645,173). The analyses focus on: length of stay, Diagnosis Related Groups (DRG), Major Diagnosis Categories (MDC), and effective Case Mix Index (CMI). Results The length of stay in the IPD (M = 5.38 ± 7.31) was significantly shorter than the DRG defined length of stay (M = 5.8 ± 4.71; p < .001; d = − 0.07) and did not exceed or undercut the DRG covered length of stay. Compared to the entirety of all pediatric departments (M = 4.74 ± 6.23) the length of stay was significantly longer in the in the IPD (p <. 001; d = 0.12). The effective CMI in IPD and all pediatric departments were identical (M = 0.76). The frequencies of DRG and MDC differed between IPD and all pediatric departments, with higher frequencies of DRGs and MDCs associated with chronic and severe illnesses in the IPD. Conclusions Treatment within integrative anthroposophic pediatric departments fits well in terms of the DRG defined conditions concerning length of stay, even though integrative pediatric patients has an increased length of stay of averagely 1 day, which is most likely associated to time consuming, complex integrative treatment approaches and to a certain extend to higher amount of chronic and severe diseases.